Assessment of Nutritional Status of Rainfed Rice in Benin Using Diagnosis and Recommendation Integrated System - Anago, F.N.; Dagbenonbakin, G. D.; Oussou, B. T. C.; Agbangba, E. C.; SAÏDOU, Aliou; AMADJI, Guillaume Lucien (My University, 2020)
The fertilizer used in Benin by rainfed rice farmers, doesn’t meet the required expectation because of lack of many essential agronomic information to formulate the appropriate nutrient compositions. Despite all the advances in improvement of rice production, its yields in traditional cropping systems are very low and the only inputs of Nitrogen, Phosphorous and Potassium do not effectively increase rice yields. The purpose of this study was to assess nutritional status of rice crops in Benin. The study covered the rainfed rice production areas of Benin Center where 72 leaves samples were taken on 3600 plants from the farmer fields. The concentrations of nitrogen, phosphorus, potassium, calcium, magnesium, iron and zinc were determined in leaves samples. The preliminary DRIS (Diagnosis and Recommendation Integrated System) norms for the rainfed rice growing in the Benin center were selected for various nutrient ratios obtained from the high yield population of the rainfed rice crop. The yields of the two subpopulations were significantly different (p < .0001). The nutrient requirement for the rainfed rice production was ranked as N> Fe> Zn>K>Mg>P>Ca. The DRIS-derived sufficiency ranges for N, P, K, Ca and Mg from the nutrient indexing survey of the rainfed rice plants grown in Benin center were 1.91-3.66, 0.30-0.64, 2.00- 3.89, 0.37-1.05 and 0.18-0.38g kg-1 respectively. The limits for Fe and Zn were 89.27-206.3 and 8.21-24.91 mg kg-1 respectively. On the basis of sufficiency ranges, 4.22, 57.75, 66.20, 56.34, 45.07, 46.50 and 29.57% of samples were low in N, P, K, Ca, Mg, Fe and Zn respectively. The DRIS norms put emphasis on nutrient balance and help to differentiate between healthy and unhealthy rice plants from the nutrition status. However, it needed further researches to determine the amount of the fertilizers to supply in order to maintain nutrient balance.
Keywords: DRIS indices; high yielding subpopulations; sufficiency ranges; rainfed rice.